Factors Influencing Intention of Yemenis to Adopt Internet Banking - Homaid, Abdo Ali Abdullah (2010)
The aim of this study is to identify factors that influence intention to adopt internet banking in Yemen. The theoretical framework of the study is based on modified version of Technology Acceptance Model (TAM). This study develops a technology acceptance model for internet banking in the form of a conceptual framework to explain the factors influencing Yemenis intention to adopt internet banking. The model employs perceived usefulness (PU), perceived ease of use(PEOU), computer self-efficacy (CSE), facilitating conditions (FC) and perceived credibility (PC). The results suggest that CSE and FC had a significant relationship with behavioral intention, FC had a significant relationship with both PEOU and behavioral intention and PU had the most significant relationship with behavioral intention. However, PC does not have relationship with PEOU. In addition, PEOU had a significant negative relationship with behavioral intention.